Morphometry of glaciovolcanic edifices from Iceland: Types and evolution - Pedersen, Gro B.M.; Grosse, Pablo; Gudmundsson, Magnús T. (Geomorphology)
The morphology of glaciovolcanoes is considered one of the distinctive characteristics of their ice-confining eruption environment. However, a thorough morphometric analysis of a large number of glaciovolcanic edifices has never been performed. Based on semi-automatic geomorphometric mapping, we present a morphometric database of 155 glaciovolcanic edifices within the Icelandic neovolcanic zones, formed during the last 0.78 Ma. This database enables a comprehensive analysis of the morphometric diversity of a large suite of glaciovolcanic edifices. Sheet-like formations, however, are not considered due to lack of data. Using three planimetric measurements (basal length, average basal width and average summit plateau width) and their ratios, three main morphometric groups can be distinguished in a ternary diagram: 1) conical edifices with no or small summit plateaus, 2) linear ridges and 3) flat-topped edifices (subdivided into equidimensional and elongated). All three groups contain edifices with and without lava caps. These morphometric groups can be fitted to the commonly accepted terminology for cone/mound, tindar and tuya. However, since lava caps occur in all morphometric groups, a grouping based on its existence is not practical. This suggests that by adding the descriptor “lava-capped” to any of the three classes may be a useful way to refine the classification. Based on the ternary diagram, ridges are the most morphometrically distinct glaciovolcanic edifice, because of their extreme elongation, followed by flat-topped edifices and finally conical edifices. However, morphometric parameters cannot be used singlehanded to identify glaciovolcanic edifices from other types of volcanic edifices such as composite volcanoes, shields or submarine volcanoes, and should always be complemented with other observations. The glaciovolcanic edifice volumes range from 0.15 · 10−2 km3 to 32 km3. Conical edifices are the smallest (<0.1 km3) and the group of flat-topped edifices has the largest edifices (>1 km3). ...